2014
DOI: 10.1096/fj.13-247635
|View full text |Cite
|
Sign up to set email alerts
|

Lamin B1 overexpression increases nuclear rigidity in autosomal dominant leukodystrophy fibroblasts

Abstract: The architecture and structural mechanics of the cell nucleus are defined by the nuclear lamina, which is formed by A- and B-type lamins. Recently, gene duplication and protein overexpression of lamin B1 (LB1) have been reported in pedigrees with autosomal dominant leukodystrophy (ADLD). However, how the overexpression of LB1 affects nuclear mechanics and function and how it may result in pathology remain unexplored. Here, we report that in primary human skin fibroblasts derived from ADLD patients, LB1, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 59 publications
(90 reference statements)
9
71
0
Order By: Relevance
“…In addition to regulating nuclear shape and stiffness [27,3942], they play important roles in chromatin organization, DNA damage repair, and transcriptional regulation [37,43,44]. Cell-stretching and micropipette aspiration experiments indicate that A-type lamins have a larger impact on nuclear stiffness than B-type lamins—nuclear stiffness strongly scales with expression of lamins A/C [3942], although increased expression of lamin B1 can also increase nuclear rigidity [45]. Consistent with the ‘nuclear barrier’ hypothesis, recent studies found that cells with reduced levels of lamins A/C have more deformable nuclei and migrate faster through tight spaces than control cells with normal lamin A/C levels [18,46].…”
Section: The Size and Rigidity Of The Nucleus: A Physical Barrier Formentioning
confidence: 99%
“…In addition to regulating nuclear shape and stiffness [27,3942], they play important roles in chromatin organization, DNA damage repair, and transcriptional regulation [37,43,44]. Cell-stretching and micropipette aspiration experiments indicate that A-type lamins have a larger impact on nuclear stiffness than B-type lamins—nuclear stiffness strongly scales with expression of lamins A/C [3942], although increased expression of lamin B1 can also increase nuclear rigidity [45]. Consistent with the ‘nuclear barrier’ hypothesis, recent studies found that cells with reduced levels of lamins A/C have more deformable nuclei and migrate faster through tight spaces than control cells with normal lamin A/C levels [18,46].…”
Section: The Size and Rigidity Of The Nucleus: A Physical Barrier Formentioning
confidence: 99%
“…The major component in regulating the structure and integrity of the NE are lamins [24, 36], with reduced levels of lamin A/C resulting in more deformable nuclei that are more prone to NE rupture [7, 10, 24, 3638]. While the B-type lamins, lamins B1 and B2, have a less pronounced effect on nuclear stiffness [36, 39], loss of B-type lamins increases the likelihood of nuclear bleb formation and NE rupture [6, 7, 9, 40]. Even in cells expressing B-type lamins, nuclear membrane blebs form at sites with openings in the lamin B-network [7, 8].…”
Section: Mechanically Induced Nuclear Envelope Rupturementioning
confidence: 99%
“…Accordingly, cells migrating in 3D collagen matrices show extensive nuclear deformation when MMP activity is inhibited, and sufficiently small pore sizes can lead to complete stalling of cell movement as the nucleus becomes ‘trapped’ in the dense network (Wolf et al, 2013). The deformability of the nucleus is largely determined by expression of A-type lamins (Lammerding et al, 2006; Lammerding et al, 2004; Pajerowski et al, 2007; Schape et al, 2009), although changes in B-type lamin expression can also impact nuclear elasticity (Ferrera et al, 2014; Swift et al, 2013). As a result, cells with decreased lamin A/C levels migrate significantly faster through narrow constrictions in microfluidics devices and transwell plates with 3 µm pore sizes (Davidson et al, 2014; Harada et al, 2014; Shin et al, 2013).…”
Section: The Nuclear Envelope In Migration Invasion and Metastasismentioning
confidence: 99%